Two new species of Tylototriton from Thailand (Amphibia: Urodela: Salamandridae) - Nishikawa, Kanto; Khonsue, Wichase; Pomchote, Porrawee; Matsui, Masafumi (Zootaxa, 2013)
Three morphological groups are found in a salamandrid newt Tylototriton shanjing from Thailand. We describe two of them as new species, one from northern and the other from northeastern Thailand, based on molecular and morphological data, however we could not make a taxonomic decision on the remaining one group because of the lack of voucher specimens and sufficient genetic data. The northern species differs morphologically from all known congeners by having the combination of orange to reddish brown markings, narrow and sharply protruding dorsolateral bony ridges on head, weakly segmented vertebral ridge, and long and high tail. The northeastern species is characterized by having the combination of yellow, orange, or reddish brown markings, wide and moderately protruding dorsolateral bony ridges on head, smooth vertebral ridge, black limbs, and black tail except for edges. Validity of taxonomic subdivision of the genus Tylototriton is discussed.